Особливості підтримки стійкості вертикального положення тіла юних спортсменів із плоскостопістю, які займаються таеквон-до - Данищук, Андрій; Danyschuk, Andriy (Східноєвропейський національний університет імені Лесі Українки, 2019)
Мета роботи – визначити ступінь порушення рівноваги під впливом субмаксимального аеробного наван-таження на м’язи нижніх кінцівок у спортсменів 7–14 років із плоскостопістю. Методика. Досліджено вплив субмаксимального аеробного навантаження на стійкість вертикальної постави в спортсменів, які займають-ся таеквон-до, у віці 7–14 років із плоскостопістю І–ІІ ступенів (n = 25) і без порушення склепінчастого апарату стопи (n = 25). Регуляцію вертикальної пози досліджували за допомогою комплексу для аналізу функціональних здібностей опорно-рухового апарату «DIERS FAMUS» ( «Німеччина»). Результати. Показано, що фізичне навантаження збільшує лінійну швидкість коливань центра тиску на стопу в обох групах спортсменів. Однак період відновлення стійкості вертикальної постави був меншим у групі юних спортсменів без ознак плоскостопості. Після фізичного навантаження на одну стопу період зниженої стійкості верти-кальної постави був більшим у юних спортсменів із плоскостопістю, порівняно з контрольною групою: 3 хв – 1 хв 50 с після фізичного навантаження. Стійкість вертикальної постави в спортсменів із плоскостопістю в середньому була нижчою, ніж у респондентів без порушення склепінчастого апарату стопи. Висновок. Регуляція вертикальної пози юних спортсменів, які займаються таеквон-до, із плоскостопістю під впливом фізичного навантаження погіршується більшою мірою, ніж у їхніх однолітків без ознак порушення склепін-частого апарату стопи, що пов’язано з асиметрією тонусу м’язів гомілки, які належать до різних міофасці-альних кінематичних ланцюгів. Специфічне тренування у вправах таеквон-до вдосконалює систему постураль-ної регуляції й підвищує швидкість її відновлення після фізичного навантаження в юних спортсменів із плоско-стопістю.The Objective of the work is to determine the degree of imbalance under the influence of submaximal aerobic exercise on posturally significant muscles of the lower extremities in athletes aged 7–14 years old with flat-footedness. Methods. The influence of submaximal aerobic load on the lower limbs on the stability of the vertical posture of athletes at the age of 7–14 years with flat-footedness of the І-ІІ degree (n = 25) who are engaged in taekwon-do and without violation of the arches of the foot (n = 25) was studied. The regulation of the vertical posture was investigated using the complex for the study of the functional abilities of the musculoskeletal system «DIERS FAMUS» («Germany»). Results. It is shown that physical activity increases the linear velocity of the oscillations of the pressure center in both groups. The recovery period of vertical posture stability was less in the group of young athletes with no flatfoot signs. After exercise on one leg, the period of reduced stability of the vertical posture was longer for young athletes with flat-footedness than in the control group: 3 minutes compared to the control group – 1 minute 50 seconds after the exercise. The stability of the vertical posture in athletes with flat-footedness was on average lower than in athletes without violating the arches of the foot (p <0,05). Conclusion. Regulation of the vertical posture of young athletes engaged in taekwon-do with flat-footedness under the influence of physical stress worsens to a greater extent than those of their peers without signs of violation of the arch of the foot, which is associated with asymmetry of the tone of the shin muscles belonging to different myo-fascial kinematic chains. Specific training in the taekwon-do exercises improves the system of postural regulation and increases the speed of its recovery after exercise in young athletes with flat-footedness
Features of Maintaining the Stability of the Vertical Body Position of Young Athletes with Flat Feet, Who are Engaged in Taekwon-do
Keywords: стабілографія; таеквон-до; фізичне навантаження; плоско-стопість; спортсмени 7–14 років; stabilography; physical activity; athletes aged 7–14 years old; taekwon-do; flatfoot